Порядок врахування стратегічних цілей бізнесу при підготовці бюджетів компанії - Давидюк, Тетяна Вікторівна; Татаринов, О. В. (Таврійський державний агротехнологічний університет імені Дмитра Моторного, 2024)
У статті проаналізовано порядок врахування під час підготовки бюджетів стратегічних цілей бізнесу, зокрема, визначено процедуру стратегічного планування в компанії, що визначає цільові стратегічні показники, зовнішні характеристики стратегічного плану, фінансовий план, балансування та коригування стратегічного плану. Особлива увага приділена річному плануванню з урахуванням довгострокових цілей компанії з деталізацією бюджетів на місяці.

Attempts by managers to develop and implement such enterprise management technologies as budget planning, KPIs, and management by objectives often end in failure because they are not interconnected. If the owners have defined targets and a strategy for the company's development, the task of the financial service is to “digitize” it. The company's key performance indicators and development prospects are detailed in annual plans and communicated to functional units with details for shorter calendar periods. The company's planning system is becoming a cross-cutting one, i.e., it combines the development of interrelated strategic, annual and operational plans. The purpose of this article is to develop an algorithm that allows linking strategic business goals with the management of financial and economic activities of a company with details at each level (horizon) of planning. Strategic (long-term) plans are developed for 5 10 years and are reviewed and approved annually. In the course of developing long-term plans, the Group sets targets for key performance indicators and external parameters of the plan (inflation, exchange rates, etc.), and develops corporate and functional strategies and a financial plan. If necessary, the strategic plan is rebalanced and adjusted based on the results of the analysis and monitoring of the implementation of the targets. The introduction of an end-to-end planning system allows a company to combine strategy, business objectives, long-term and short-term goals, performance criteria and action programs into a single whole and manage its business, promptly responding to changes in the external and internal business environment.
The procedure for taking into account strategic business goals when preparing company budgets
Keywords: стратегічні показники; бюджетування; фінансове планування; річні бюджети; центри відповідальності; strategic indicators; budgeting; financial planning; strategic planning; annual budgets; responsibility centers